A participatory diagnostic study of the oil palm (Elaeis guineensis) seed system in Benin - AKPO, Essegbemon; VISSOH, VINASSÉHO PIERRE; TOSSOU, COCOU RIGOBERT; CRANE, TODD; KOSSOU, KODJO DANSOU; RICHARDS, P. (My University, 2012)
A participatory diagnostic study of the oil palm (Elaeis guineensis Jacq.) seed system (OPSS) was conducted along a gradient of rainfall and distance to the oil palm research centre across the oil palm growing belt of Benin. The objective was to identify, jointly with key actors, the constraints in the OPSS and to assess the performance of the OPSS from a farmers’ perspective. The methodology included introductory community meetings, group discussions, individual in-depth interviews, field visits and a validation workshop with the key actors. Farmers indicated that the current OPSS does not perform well. Major constraints include the poor geographic distribution of authorized nurseries, poor genetic quality of the material on plantations, high cost of hybrid planting material, and poor seedling care in nurseries, leading to poor physiological quality. The poor physiological quality was specifically mentioned in relation to authorized nurseries in the east of our study area, whereas farmers in the west and centre were more concerned about the uncertain genetic quality of the planting material. The constraints indicate the need for further research to understand the historical context of OPSS development, joint experimentation to improve seedling management practices in authorized nurseries and joint identification of the (genetic) quality of oil palm seedlings, using morphological and molecular characteristics and tools. The study also identified potential opportunities for institutional intervention: redefinition of the procedure of establishing authorized oil palm nurseries, formalization of currently non-authorized nurseries, ISO certification of authorized nurseries and social communication.
Keywords: Institutional change; Planting material; Seed quality; Seed systems; Benin